2015
DOI: 10.4315/0362-028x.jfp-14-531
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus in Raw Milk: Prevalence, SCCmec Typing, Enterotoxin Characterization, and Antimicrobial Resistance Patterns

Abstract: Staphylococcus aureus is a known major cause of foodborne illnesses, and raw milk and dairy products are often contaminated by enterotoxigenic and antimicrobial-resistant S. aureus strains. In the present study, 35 S. aureus strains were isolated from 383 raw milk samples collected from various dairy herds in the province of Milan (northern Italy). The isolates were characterized based on their antimicrobial susceptibility patterns and the presence of genes encoding staphylococcal enterotoxins (sea, seb, sec, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 35 publications
6
45
10
2
Order By: Relevance
“…34 Findings of the existing investigation revealed that the contamination rate of milk samples was 4.74% (28/590). Incidence of the MRSA in raw milk samples in our survey was lower than those of Italy (20%) 35 and Turkey (17%), 36 while it was higher than those of England (2.30%) 37 and Germany (2.30%). 38 Investigations conducted in the US along with other countries, including North America, Canada, Africa, Asia and Europe, have recovered MRSA mostly from dissimilar kinds of food and dairy samples.…”
Section: Discussioncontrasting
confidence: 66%
“…34 Findings of the existing investigation revealed that the contamination rate of milk samples was 4.74% (28/590). Incidence of the MRSA in raw milk samples in our survey was lower than those of Italy (20%) 35 and Turkey (17%), 36 while it was higher than those of England (2.30%) 37 and Germany (2.30%). 38 Investigations conducted in the US along with other countries, including North America, Canada, Africa, Asia and Europe, have recovered MRSA mostly from dissimilar kinds of food and dairy samples.…”
Section: Discussioncontrasting
confidence: 66%
“…Daka et al (2012) (Daka et al, 2012) and higher from other (Vyletelova et al, 2011, Paterson et al, 2012, Kanaan and Al-Shammary 2013, Riva et al, 2015, Cortimiglia et al, 2016. The reports on the prevalence of MRSA in milk and dairy products vary significantly between different studies and different countries or even among regions within the same country where they carried out and even among herds within the same region.…”
Section: Discussionmentioning
confidence: 98%
“…DG Amoako, AM Somboro, AL Abia, C Molechan, K Perrett, LA Bester and SY Essack[26] reported that the S. aureus bacteria isolated from poultry products harbored the highest incidence of resistance toward tetracycline(61.67%), penicillin G (55.83%), erythromycin (54.17%), clindamycin (43.33%), rifampicin (40.83%), doxycycline (36.67%), ampicillin (34.17%), amikacin (30.83%), moxi oxacin (30.83%), trimethoprim-sulfamethoxazole (30.00%), levo oxacin (23.33%), cipro oxacin (15.83%), gentamicin (8.33%) and cefoxitin (7.50%). Surveys conducted on America, Asia, Africa, and Europe continents revealed the high incidence of antibiotic resistant-S. aureus in foods with animal origins[27,28]. Similar pattern of resistance of S. aureus bacteria isolated from different kinds of foodstuff and clinical samples have been reported toward uoroquinolones, aminoglycosides, macrolides…”
mentioning
confidence: 63%